ENHANCING R&D IN TAIWANESE SMALL AND MEDIUM ENTERPRISES: AN ANALYSIS OF POST COVID-19 BUSINESS SURVIVAL STRATEGIES - Robert Stalone Buwule; Tony Kuo (International Journal of Management Studies)
The COVID-19 pandemic significantly impacted businesses, particularly small and medium enterprises (SMEs). Despite numerous setbacks, some SMEs demonstrated resilience by adopting innovative survival strategies, including investment in research and development (R&D). This study investigates the extent of R&D investment among selected SMEs in Taiwan and its role in their survival during the pandemic. Using a mixed methods approach, data was collected through semi-structured questionnaires, with participants representing various SME categories until saturation was achieved. SME proprietors provided insights on how R&D investments contributed to their resilience. The findings indicate that 73.3% of respondents invested directly in R&D and 54.3% reported that R&D investments positively impacted their business survival during the pandemic. The study recommends that SMEs enhance their R&D capabilities by developing staff skills and allocating specific funds for R&D in their budgets to better withstand future disruptions.